Improvement Of Current Reading Abilities Through Letter Card Games For Class 2nd SDN 02 Kebagusan - Rusiana, Nita (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this research is that students can read simple words and sentences fluently and accurately through letter card games. The research conducted was a Classroom Action Research (PTK) in three cycles. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle, the students who completed after carrying out the post test were 70,65%. In cycle II students who completed after carrying out the post test were 84,25%. These results indicate that reading fluently through the letter card game can improve student learning outcomes, especially Indonesian language muple at SDN 02 Kebagusan.